Record of regret a novel - Dong, Xi 1966- (Chinese literature today book series, 2018)
"Zeng Guangxian, a young man who spends his life firmly under the thumb of forces greater than himself, details the regrets of his life as bad luck and Zeng's own drive for a bigger, better future splinter his family, fortune, and social reputation."--